Equity Valuation Using Price Multiples: Evidence from India - Sanjay Sehgal,; Asheesh Pandey, (Asian Academy of Management Journal of Accounting and Finance, 2010)
In this paper, we evaluate alternative price multiples for equity valuation purposes in the Indian context. Data are taken from 145 large companies that satisfy our screening criteria. The sample companies cover 13 prominent sectors, and the study period covers the years 1990–2007. We generate price forecasts based on each multiple by regressing the historical prices on different value drivers. We use two forecast evaluation criteria, namely root mean squared error and Theil's inequality coefficient. We find that price–to-earnings provide the best price forecast compared to the other three price multiples, price-to-book value, price to cash flow and price to sales. We also develop price forecasts based on pairwise combinations of these price multiples. The value driver combination book value-sales appears to be most efficient in terms of error minimisation. However, historical price to earnings as a standalone multiple performs better in equity valuation vis à vis all combinations of value drivers. We recommend that historical price to earnings (P/E) is the best price multiple for developing price forecasts in the Indian environment. Our findings are pertinent for market participants and financial regulators. The present work contributes to emerging market literature on equity valuation.